Customer lifetime value (CLV) insights for strategic marketing success and its impact on organizational financial performance - Nafez Ali; Osama Samih Shabn (Cogent Business & Management, 2024)
This paper delves into the intricate interplay among Customer Lifetime Value (CLV), strategic marketing practices, and their impact on organizational financial performance. Aimed at informing strategic decision-making for marketers and business leaders, the study employs a mixed-methods research approach, combining quantitative and qualitative methods. Of the 375 participants invited to partake, 332 questionnaires were deemed valid for analysis. Quantitative data from customer transaction records and qualitative insights from a customized questionnaire reveal positive customer perceptions regarding CLV factors. Respondents show moderate to high agreement with statements related to product alignment, long-term outlook, repeat purchases, loyalty rewards, and customer-oriented services. The results underscore the pivotal role of CLV in influencing financial metrics, notably market valuation (P/E ratio). Recommendations include enhancing customer service, refining marketing strategies, and maintaining financial stability to bolster customer confidence.
Keywords: G11; G30; M31; M40; 650; Customer lifetime value (clV); financial performance; ROA; ROE; P/E ratio